The valorisation of platinum group metals from flotation tailings: A review of challenges and opportunities - Gibson, Borbor A.K.K.; Nwaila, Glen; Manzi, Musa; Ndlovu, Sehliselo (Elsevier, 2023)
Flotation tailings from South Africa’s platinum group minerals (PGM) represent complex polymetallic orebodies comprising a low-grade platinum group elements (PGE) content and complex mineralogical composition. Nevertheless, given the valuable mineral potential in the tailings, it is understandable that the substantial historic tailings deposits and sizeable annual production volume from primary processes represent a potential secondary resource. For several decades, valorising the PGM tailing materials received very little interest due to limitations associated with extractive metallurgical technology to achieve economically viable PGE extraction. The early 21st century saw the coming online of technologies, including but not limited to ultrafine grinding, suitable to meet challenges in primary metallurgical treatment processes to recover valuable minerals from ultrafine particle fractions, which could not otherwise be recovered. More so, such processes were critical in improving the liberation of partially liberated particles without compromising additional ultrafine generation. These technologies led to the development of re-treatment pilot tests and subsequent industrial re-treatment recovery processes. The current industrial re-treatment approach – via tertiary scavenging flotation circuits – renders profit in small increments up to 1 ~ 2% additional recovery relative to the primary plant head grade. These small increments relate to about ~12–30% PGE recovery of the feed grade to the re-treatment circuit, thereby enhancing the primary plant’s overall economics as well as aiding the supply of critical metals to meet global demands. With a focus on South Africa, this review provides an overview of (a) the current and future drivers of the precious metals global demand; (b) proffers discussion on the PGM characteristic mineralogy and the metallurgical value chain; (c) relates the parent orebodies (“reefs”) mineral characteristics to the inherent processed tailings; (d) estimates the economic potential these massive processed waste materials contain, (e) provides an overview of existing technologies that are industrially used in tailing re-treatment plants; and (f) outlines a comprehensive understanding of the nature of value minerals rejection to tailings.
Keywords: Platinum group mineral tailings; Flotation tailings; Re-treatment; Valorisation; SDG-9: Industry, innovation and infrastructure; SDG-17: Partnerships for the goals